IMPROVING STUDENT’S MATHEMATICAL PROBLEM-SOLVING ABILITY BY USING MISSOURI MATHEMATICS PROJECT AT SMP NEGERI 4 MEDAN. - Kiki Ambar Waty Malau; Mukhtar Mukhtar (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to improve students' mathematical problem-solving skills through the Missouri Mathematics Project (MMP) model on the material of a Linear Two Variable System in grade VIII-6 students of SMP N 4 Medan as a subject or this research. The type of this research is classroom action research. The instrument used the collect the data are essay test and observation sheet. Before giving the action in initial test to 32 students obtained the average score is 50.46 with the classical completeness is 34.37% or only 11 students achieve the completeness criteria. The completeness criteria is the standard point that must be reached by students namely at least 65 and classical completeness is the standard percentage that must be reached by the class namely at least 85%. After given the action in the first cycle namely the implementation of MMP learning model to 32 students, obtained the average score is 63.9844 with the classical completeness 50% or 16 students achieve the completeness criteria. Then given the second cycle namely increasing MMP learning model, obtained the average score is 82.11 with the classical completeness 93.75%. Based on the observation done by teacher obtained that the point of second cycle is higher than the point of first cycle. Based on the average gain score, obtained that the average gain score in Cycle I test-Cycle II test is higher than Initial Test-Cycle I Test. From the result of research, can be concluded that the mathematical problem-solving ability of students can be increased or improved especially on the topic of Linear System with Two Variable by using Missouri Mathematics Project Learning Model